Great ape cardiovascular disease: aetiopathogenesis, risk factors and diagnostic tools - Moittie, Sophie (2021)
Chimpanzees, orangutans, gorillas and bonobos are commonly kept in zoos across the world, and the understanding of their physiology and susceptibility to diseases is critical for the maintenance of healthy captive individuals and the protection of wild populations. Cardiovascular disease (CVD) is known as a major cause of morbidity and mortality in zoo great apes, and the Ape Heart Project has been studying its epidemiology and pathogenesis since 2014. The first chapter of this thesis critically examines the literature available related to great ape CVD and questions the possible aetiologies of this disease process. The three subsequent chapters explore possible diagnostic tools that could help with the investigation of specific risk factors of CVD in great apes, with zoo chimpanzees as models. Oscillometric and invasive blood pressure measurement devices are compared highlighting the inaccuracy of non-invasive devices when measuring blood pressure in anaesthetised chimpanzees. The value of implantable loop recorders (ILR) is also assessed to investigate the occurrence of arrhythmic events in chimpanzees considered at risk of cardiac disease, and this study demonstrates that ILRs are a valid tool for cardiac screening in great apes. The use of dried blood spots (DBS) to measure vitamin D in chimpanzees is explored in Chapter 4 and found that the analytical error is greater in DBS compared with serum samples, thus limiting the use of the DBS technique to field studies when the collection and analysis of serum samples are not achievable. Chapter 5 investigates the vitamin D status of European zoo chimpanzees and found relatively low serum vitamin D concentrations in a large contingent of this population during the low UVB season, supporting the hypothesis that vitamin D insufficiency may be a risk factor for CVD disease in great apes. Chapter 6 describes the findings of the systematic post-mortem examination of 50 great ape hearts and illustrates some differences seen between species. Finally, the last chapter of this thesis depicts the application of microcomputed tomography to formalin-fixed chimpanzee hearts and the discovery of bone formation within the cardiac skeleton of chimpanzees affected by myocardial fibrosis. Further studies investigating risk factors of great ape cardiovascular disease, especially hypertension and hypovitaminosis D, are urgently needed.